(untitled) (Fiep Bulletin - online, 2014)
Labor Gymnastics consists in physical exercises made inside the work environment, planned according to the played functions. With the objective of integrate, relax body and mind, promote the health, stimulate the practice of physical activities and prevent lesions occasioned by repetitive movements, as well as other work related lesions, Labor Gymnastics has been inserted in companies all over the world, as a support for a better quality of life of the collaborators. The present study has been developed at Gramado City Hall (RS) with the objective of identifying the influence of Labor Gymnastics in the mood states of collaborators. The quantitative descriptive paradigm was used for this study, using as a data collection the POMS (Profile of Mood States) Test, that evaluates the Profile of Mood States trough six factors: tension, depression, anger, vigor, fatigue and mental confusion. Twenty (20) collaborators of the administrative section of the main building of the City Hall participated, being 10 (ten) males and 10 (ten) females. The ages varied from 17 (seventeen) to 48 (forty-eight) years old. This study proves that the practice of Labor Gymnastics influences positively on the individuals mood states, creating healthier environments, harmonious, providing improvements in the interpersonal relationship and in the relationship with the public, bringing more joy, willingness, confidence, satisfaction and appreciation.